PPeran Aktif Suami SIAGA untuk Menurunkan Kecemasan Ibu Hamil dalam Menghadapi Persalinan - Dwi Nurjayanti (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2022)
Family support, especially the husband during pregnancy, childbirth and the baby care period as well as the recovery of the mother after giving birth can provide enthusiasm and motivation for mothers in facing the process of becoming a mother. This study aims to determine the effect of the active role of the SIAGA husband on the level of anxiety of pregnant women in facing childbirth at RSUD dr. Darsono Kab. Pacitan. The design of this study was cross-sectional. The population of this study were all normal pregnant women in the third trimester at RSUD Dr. Darsono Pacitan. The sampling technique used was accidental sampling, so that the sample size was obtained = 38 people. Data were collected through filling out questionnaires, then analyzed to test hypotheses. Based on the results of data analysis, it can be seen that the active role of SIAGA husbands is 13.9% on the level of anxiety of pregnant women in facing the delivery process. This explains that moral support from the closest person, namely the husband, is inversely proportional to the emergence of mother's anxiety in dealing with the delivery process.Keywords: husband on standby; anxiety; mother ABSTRAK Dukungan keluarga, terutama suami dalam masa kehamilan, persalinan dan masa perawatan bayi serta pemulihan ibu pasca bersalin dapat memberikan semangat dan motivasi bagi ibu dalam menghadapi proses menjadi seorang ibu. Penelitian ini bertujuan untuk mengetahui pengaruh peran aktif suami SIAGA terhadap tingkat kecemasan ibu hamil dalam menghadapi persalinan di RSUD dr. Darsono Kab. Pacitan. Rancangan penelitian ini adalah cross-sectional. Populasi penelitian ini adalah semua ibu hamil normal trimester III di RSUD Dr. Darsono Pacitan. Teknik sampling yang digunakan adalah accidental sampling, sehingga diperoleh ukuran sampel = 38 orang. Data dikumpulkan melalui pengisian kuesioner, lalu dianalisis untuk menguji hipotesis. Berdasarkan hasil analisis data dapat diketahui bahwa peran aktif suami SIAGA bernilai sebesar 13,9% terhadap tingkat kecemasan ibu hamil dalam menghadapi proses persalinan. Hal tersebut menjelaskan bahwa dukungan moril dari orang terdekat yakni suami berbanding terbalik dengan munculnya rasa cemas ibu dalam menghadapi proses persalinan.Kata kunci: suami siaga; kecemasan; ibu